Enhancing Service Recovery: How Human Capital Drives Performance with Employee Commitment as a Mediator - Saputra, Wawan Ari; Hadi, Syamsul; Chandra Kirana, Kusuma; yanuar iswantoro, ibnu; Ashakah, Felix Onoriode (SMARTINDO, 2024)
Purpose - The purpose of this study was to analyze the impact of human capital on service recovery performance through employee commitment. Design/methodology/approach - The study took place in Sleman Regency and focused on an employee at RSUP Dr. Sardjito. The sampling technique used was the Numogram Harry King's Formula method. Data analysis was descriptive. The analysis tool employed was Partial Least Square (PLS) analysis using SmartPLS 3.2.9 software, with Bootstrapping used for mediation analysis. Findings and Discussion - The study's findings show that human capital positively impacts service recovery performance and employee commitment. Employee commitment also positively affects service recovery performance and can act as a mediator between human capital and service recovery performance. Originality - The originality of this research lies in its comprehensive examination of the interrelationships between human capital, employee commitment, and service recovery performance within the healthcare sector.